Sistem Monitoring Kadar Gas Berbahaya Berdasarkan Amonia Dan Metana Pada Peternakan Ayam Broiler Menggunakan Protokol MQTT Pada Realtime System - Alfaviega Septian Pravangasta; Mochammad Hannats Hanafi Ichsan; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Broiler chicken farm is the easy-applied farm factory that always released so many waste result, which is one of them is very unpleasant-smell air pollution. This smells and air pollution is because of any gases and the other particle, especially some dangerous gas, ammonia and methane that can make some serious damage for human. For the solution, the monitoring system of ammonia and methane gas using MQTT protocol on real time system has been designed. For the input, the system use MQ-4 which can detect the ammonia gas and MQ-135 who can detect methane gas. From the sensor, data will be sent to Arduino, that later will be forwarded on wifi module ESP8266. From ESP8266, data will be sent to web server using MQTT protocol and will be displayed on Thingsboard web server on real time condition. When it tested, the execution process show that between the first process (read data from sensor) until display the data on Thingsboard is 1.95 second. The MQTT delays is 1.37 second on real time condition.